STRATEGI BISNIS USAHA KECIL DI MASA PANDEMI MENGGUNAKAN MEDIA SOSIAL - I Gusti Agung Sinta Prema Candra; Ni Putu Emilika Budi Lestari (Jurnal Nawala Visual, 2021)
In 2020, the whole world is hit by a disaster, namely a COVID-19 outbreak, this has caused many people to lose their livelihoods, and has caused an economic crisis around the world. Likewise with small businesses started by business people. Many small businesses have experienced a decrease in income due to this outbreak, where people save a lot to survive, but on the other hand there are some small businesses that have experienced an increase in turnover during the pandemic, because they apply the theory of digital marketing which makes their business turnover increase. even during a pandemic like now. The theory of digital marketing is very important to know by all business people who have small or large businesses because the impact that can be generated from marketing products online is said to be effective and much cheaper compared to offline marketing, for example with brochures and others. Advertising online is also very effective because on social media there are already segregation of consumer interests, so it is very easy for us as business people to determine the market according to the products or services we have. This research was conducted because many business people still do not understand how to market their wares through social media, the purpose of this research is that small business people who read this can understand how to market their products with digital marketing theory and can increase business turnover.